2010
DOI: 10.1115/1.4000685
|View full text |Cite
|
Sign up to set email alerts
|

Through-Plane Permeability for Untreated and PTFE-Treated Gas Diffusion Layers in Proton Exchange Membrane Fuel Cells

Abstract: The through-plane permeability has been experimentally measured for untreated and polytetrafluoroethylene-treated (PTFE-treated) gas diffusion layers (GDLs), as used in proton exchange membrane fuel cells. Contrary to what the literature has previously shown, the results suggest that there exists an optimum value for the wet-proofing agent, PTFE, at which the though-plane permeability of the GDL is a maximum. The analysis that is undertaken to investigate the effect of the air compressibility shows that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…Temperature T is measured by the thermocouple connected to the fuel cell test station and the viscosity of air is calculated by the Sutherland's empirical formula [15]. When the air velocity is low, the permeability can be obtained by fitting Eq.…”
Section: Data Analysis Of Effective Permeability and Inertial Coefficmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature T is measured by the thermocouple connected to the fuel cell test station and the viscosity of air is calculated by the Sutherland's empirical formula [15]. When the air velocity is low, the permeability can be obtained by fitting Eq.…”
Section: Data Analysis Of Effective Permeability and Inertial Coefficmentioning
confidence: 99%
“…Besides, when the in-plane permeability was measured, the exclusion of the non-Darcy terms resulted in a significant error, especially at high flowrates. Ismail et al [15] also investigated the through-plane permeability for untreated and PTFE-treated GDLs. They found that there was an optimum value of PTFE loading, at which the through-plane permeability was a maximum.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies 3,7,10,25 reported about increasing ohmic losses with higher coating levels due to the additional unconductive coating. In contrast to this, Chang et al 16 reported about constant ohmic losses between coating loads of 5 and 20 wt% PTFE.…”
mentioning
confidence: 99%
“…Water permeation measurements also have shown that a higher coating load results in an increased capillary pressure threshold. 9 Ismail et al 10 assumed that a reduction in the average pore size may not only decrease the permeability but may also increase the permeability under certain conditions. LaManna and Kandlikar 8 found out that a higher coating load causes a higher tortuosity, resulting in increased three-dimensional diffusion pathways for water vapor.…”
mentioning
confidence: 99%